AKTIVITAS BELAJAR SISWA DI LUAR KELAS DI MADRASAH TSANAWIYAH AL-MUTTAQIN PEKANBARU RIAU. - Nurhadi Nurhadi; Zainul Bahri Lubis (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study stood out of two variables, namely learning activities as X variables (independent/independent variables) and outside of class Y (dependent variable). The formulation of the problem in this study is how learning activities outside the classroom at Madrasah Tsanawiyah Al-Muttaqin Pekanbaru Riau. The purpose of this study was to find out the learning activities outside the classroom at Madrasah Tsanawiyah Al-Muttaqin Pekanbaru, Riau. The population in this study were all students of Madrasah Tsanawiyah Al-Muttaqin Pekanbaru Riau which numbered 385 people. The sample in this study focused on students of class VII and VIII with consideration of class IX UN preparation, which amounted to 80 people. Data collection in this study uses questionnaires, observation, and documentation. Based on data processing, the results showed that the learning activities at Madrasah Tsanawiyah Al-Muttaqin Pekanbaru Riau were in the category of